Nanomaterials Enhanced Sonodynamic Therapy for Multiple Tumor Treatment - Yang, Mengyao; Wang, Xin; Peng, Mengke; Wang, Fei; Hou, Senlin; Xing, Ruirui; Chen, Aibing (Nano-Micro Letters, 2025)
Sonodynamic therapy (SDT) as an emerging modality for malignant tumors mainly involves in sonosensitizers and low-intensity ultrasound (US), which can safely penetrate the tissue without significant attenuation. SDT not only has the advantages including high precision, non-invasiveness, and minimal side effects, but also overcomes the limitation of low penetration of light to deep tumors. The cytotoxic reactive oxygen species can be produced by the utilization of sonosensitizers combined with US and kill tumor cells. However, the underlying mechanism of SDT has not been elucidated, and its unsatisfactory efficiency retards its further clinical application. Herein, we shed light on the main mechanisms of SDT and the types of sonosensitizers, including organic sonosensitizers and inorganic sonosensitizers. Due to the development of nanotechnology, many novel nanoplatforms are utilized in this arisen field to solve the barriers of sonosensitizers and enable continuous innovation. This review also highlights the potential advantages of nanosonosensitizers and focus on the enhanced efficiency of SDT based on nanosonosensitizers with monotherapy or synergistic therapy for deep tumors that are difficult to reach by traditional treatment, especially orthotopic cancers. Highlights: 1 The main mechanisms and clinical potential of sonodynamic therapy are emphasized. 2 The nanomaterials provide new prospects and development directions for enhancing the treatment of cancer. 3 Recent developments of sonodynamic therapy for deep tumors that are difficult to reach by traditional treatment, especially orthotopic cancers.